Insufficient accuracy of the ultrasound-based determination of the achilles tendon crosssectional area - Bohm, S.; Mersmann, F.; Schroll, A.; Arampatzis, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The accurate assessment of the Achilles tendon cross-sectional area (CSA) is a crucial prerequisite to investigate morphological tendon plasticity and to calculate the tendon Young`s modulus (i.e. material properties) (Arampatzis et al., 2007). Besides the established magnetic resonance imaging (MRI), ultrasonography emerged as an alternative imaging technique for the measurement of the tendon CSA. The purpose of the present study was to assess the objectivity and reliability of the ultrasound-based methodology and its validity with respect to an MRI-based assessment. Methods: The Achilles tendon CSA of 17 healthy male participants (27.8 ± 3.9 yrs., 180.3 ± 6.7 cm, 76.3 ± 8.5 kg) was assessed by means of ultrasonography at the proximal, medial and distal position of the free tendon five times each on two separate days and three independent observers segmented the CSAs. For the validation, MRI-based CSA measurements were provided accordingly. Results: The objectivity and reliability analysis of the ultrasound-based method revealed significant observer and measurement day effects (p < 0.05), despite high intra-class correlation coefficients for the three observers (>0.93) and for both days (>0.89), respectively. The typical percentage error between both days was in average 7.1%. Comparing both methods, ultrasonography underestimated (19% in average) the CSA values obtained by MRI (p < 0.05). Although the correlation coefficients of both methods were high in all three positions (>0.88), the respective range of the limits of agreement (Bland and Altman, 1986) of up to +28 mm² and -2 mm² evidence considerable inconsistency. Discussion: The results of the present study provide evidence of strong limitations of the ultrasound-based Achilles tendon CSA determination methodology regarding the three mayor test quality criteria. Besides the dependency of the CSA determination from the observer, the ultrasound method is not sensitive enough to detect physiological changes in Achilles tendon morphology, as reported for longitudinal intervention studies (Arampatzis et al., 2007; Bohm et al., 2014). Furthermore, the validity analysis revealed a lack of agreement between both methods, since the ultrasound technique provided CSA values from 36% below to 3% above (i.e. relative limits of agreement) those determined by MRI as the accepted gold standard. Therefore, the ultrasoundbased methodology cannot be recommended for the accurate Achilles tendon CSA determination in vivo.